2020
DOI: 10.1177/0300060520926411
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated corneal collagen cross-linking in clinical management of infectious keratitis

Abstract: Objective To evaluate the clinical efficacy of corneal collagen cross-linking (CXL) in the treatment of infectious corneal diseases. Methods This study retrospectively analyzed the clinical efficacy of CXL in 65 eyes with infectious keratitis in Jinan Second People’s Hospital from December 2016 to June 2018. During 6 months of follow-up after CXL treatment, the results of confocal microscopy and anterior segment optical coherence tomography, as well as visual acuity and corneal biomechanical parameters, were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Li, et al (2020) 10 showed that patients with infectious keratitis who underwent corneal collagen cross-linking (CXL) had an overall cure rate of 93.85% (94.12% in the case of fungal keratitis and 91.67% in the case of bacterial keratitis); there was no discernible difference in the cure rates between the two groups. The groups with baseline ulcer sizes 4 mm x 4 mm and those with baseline ulcer size 4mm x 4mm to 7mm x 7mm; had cure rates of 95.23% and 91.30%, respectively; there was no statistically significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Li, et al (2020) 10 showed that patients with infectious keratitis who underwent corneal collagen cross-linking (CXL) had an overall cure rate of 93.85% (94.12% in the case of fungal keratitis and 91.67% in the case of bacterial keratitis); there was no discernible difference in the cure rates between the two groups. The groups with baseline ulcer sizes 4 mm x 4 mm and those with baseline ulcer size 4mm x 4mm to 7mm x 7mm; had cure rates of 95.23% and 91.30%, respectively; there was no statistically significant difference between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…Patients undergoing an accelerated (fast) PACK-CXL protocol in the present study were less likely to experience treatment failure, meaning that acceleration could be a potential “success factor”. Effectiveness of accelerated PACK-CXL was previously described in case reports of infectious keratitis in dogs and cats [ 3 , 45 ], and in human patients [ 46 , 47 ]. These reports, however, did not include comparison groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of corneal crosslinking in the management of mycotic keratitis remains controversial in humans with different studies providing conflicting results. Some case reports [162][163][164][165] and major studies [159,166,167] have shown corneal crosslinking to be a useful adjunctive therapy for managing fungal keratitis. However, the Cross Linking Assisted Infection Reduction Trial (CLAIR trial), a randomised control trial [159] done to evaluate the role of corneal collagen crosslinking in the management of fungal keratitis concluded that it has no added advantage and furthermore suggested that crosslinking can result in inferior visual outcomes when compared with standard medical management in fungal keratitis.…”
Section: Photo Activated Chromophore For Keratitismentioning
confidence: 99%